COVID-19, the trauma of the 'real' and the political import of vulnerability. (1st February 2022) - Ghandeharian, Sacha; FitzGerald, Maggie
Abstract : Politics in the neoliberal/modern/Western world is structured based upon the assumption that political subjects are atomistic and self-sufficient; these assumptions suppress and deny (inter) dependency, relationality and vulnerability. Yet, the rapid spread of COVID-19 has devastated many communities, drastically changed political and social life, and foregrounded the ways in which vulnerability is an inescapable fact of our existence. Drawing upon Žižek's reading of Lacan's notion of the 'real' and the ethics of care, we analyse the COVID-19 pandemic so as to argue that vulnerability must be understood as a fundamental political concept that merits ongoing attention in our political systems.